Biophysical Properties of Lumbricus terrestris Erythrocruorin and Its Potential Use as a Red Blood Cell Substitute - Elmer, Jacob (MDPI, 2012)
Previous generations of hemoglobin (Hb)-based oxygen carriers (HBOCs) have been plagued by key biophysical limitations that result in severe side-effects once transfused in vivo, including protein instability, high heme oxidation rates, and nitric oxide (NO) scavenging. All of these problems emerge after mammalian Hbs are removed from red blood cells (RBCs) and used for HBOC synthesis/formulation. Therefore, extracellular Hbs (erythrocruorins) from organisms which lack RBCs might serve as better HBOCs. This review focuses on the erythrocruorin of Lumbricus terrestris (LtEc), which has been shown to be extremely stable, resistant to oxidation, and may interact with NO differently than mammalian Hbs. All of these beneficial properties show that LtEc is a promising new HBOC which warrants further investigation.